2018
DOI: 10.3390/c4040054
|View full text |Cite
|
Sign up to set email alerts
|

A Metal-Free Carbon-Based Catalyst: An Overview and Directions for Future Research

Abstract: Metal-free carbon porous materials (CPMs) have gained the intensive attention of scientists and technologists because of their potential applications, ranging from catalysis to energy storage. Various simple and facile strategies are proposed for the preparation of CPMs with well-controlled sizes, shapes, and modifications on the surface. The extraordinary tenability of the pore structure, the environmental acceptability, the unique surface and the corrosion resistance properties allow them to be suitable mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 190 publications
(222 reference statements)
0
24
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] However, the use of noble metals raises doubts about the overall sustainability of the process, hence, pointing towards alternative metal free analogues. [12][13][14] Carbon-based catalysts are attracting significant attention to reduce the use of metals in heterogeneous catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] However, the use of noble metals raises doubts about the overall sustainability of the process, hence, pointing towards alternative metal free analogues. [12][13][14] Carbon-based catalysts are attracting significant attention to reduce the use of metals in heterogeneous catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1). [18][19][20][21][22][23][24][25][26][27][28][29] However, pristine carbon materials are inert because uniform charge distribution which is the common property of all carbon materials blocks the electron transfer and decreases the interaction between the carbon materials and the reactants. [30][31][32] Introducing heteroatoms like nitrogen, phosphorus, boron, and sulfur into sp 2 -hybridized carbon frameworks can cause the charge delocalization and change of the electronic structure into metal-like, which helps to obtain signicant catalytic performance in a similar way of metal-based catalyst or can be applied as a superior alternative to the metal catalyst in industrial processes.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…In the past few years, several reviews have been published toward the applications of carbon-based materials especially N-doped carbons in heterogeneous catalysis. 7,8,23,[50][51][52] However, a comprehensive review that covers the application of various metal-free heteroatom-doped carbon catalysts (including single-element B-, N-, S-, and P-doped, dualelements doped, and triple-elements doped carbon catalysts) in the eld of organic transformations is highly desirable.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Recently, the use of Pd NPs as sensors and catalysts has been investigated due to their remarkable properties. [32][33][34][35][36][37] It is of great interest that Pd NPs are obtained by the green synthesis method for catalysis, sensors, and biological applications. It has been found that Pd NPs synthesized by the green synthesis method have outstanding antioxidant properties, but their activity is not yet fully determined.…”
Section: Introductionmentioning
confidence: 99%